Changes in Microclimate Due to the Properties of Landscape Materials: A Case Study in a Coastal City of a Tropical Area - Sangkertadi Sangkertadi; Supardjo S; Zahra Z; Suriandjo H. S (Journal of World Science, 2025)
The objective of this study is to determine the role of landscape materials in microclimate changes within a tropical humid environment, specifically in coastal areas. Landscape materials possess thermophysical properties that can influence microclimate changes. This study focuses on three microclimate variables: surface temperature, air temperature and solar radiation. The landscape materials examined include bricks, dry` soil, paving stones, trees, and a garden pond. A quantitative descriptive analysis method was employed. Thermophysical properties of local materials, such as red bricks and paving blocks, were measured using a calorimeter, infrared thermometer, and thermocouples. Microclimate measurements were conducted in the open space of a commercial zone at coastal area of Manado City, Indonesia. The measurement include solar radiation, air temperature, and surface temperature of various materials. The HEAT2 computer program was used to assist in analyzing changes in surface temperature due to the presence of different landscape materials. The results revealed that at midday, trees could reduce solar radiation by up to 80% under their shade. Conversely, materials like bricks, paving stones, and hard soil, when exposed to direct sunlight, could cause surface temperatures to reach up to 50°C. The surface temperature of the garden pond water could reach 50°C, but at a depth of 50 cm, the temperature dropped to 25°C.